Politik Pembangunan Ekonomi di Malaysia: Analisis Terhadap Islam Hadari - MUHAMMAD SYUKRI SALLEH (Universitas Sumatera Utara, 2012)
This is a study of the politics of economic development in Malaysia. Especially concept of Islam Hadhari as general concepts and principles of Economic Development that promotes balance and completeness. This study explain that Islam Hadhari is an approach based on Islamic. It’s has an extra meaningful as development stratgy. This study discusses about how many aspects which is still needs to be reachable clearly from the concept Islam Hadari. Collecting data of this study is using library research. This study found there are five aspects who still need to explained. First, defenition abut “balanced” and “comprehensive”; Second, the theoretical basis of economic development of Islam Hadhari; Third, the understanding and implementation methods; Fourth, index of accomplishment; And, fifth, the position of Islam Hadari in Malaysian development strategy. If the concept of Islam Hadari used as an approach to development, it will have an impact on political policies that refer to Islamic values.Keywords: Political development, Islam hadari, economic development.